Perspectives of Nursing Students toward High-Fidelity Simulation Learning During COVID-19 Pandemic: Simulation-based learning in Covid-19 - Abu Shosha , Ghada; Al-Kalaldeh, Mahmoud (International Journal of Practice-based Learning in Health and Social Care, 2024)
While evidence of the impact of simulation in nursing education is growing, COVID-19 pandemic may carry further evaluation beyond the existing perception. To explore Jordanian nursing students' perspectives toward utilizing high-fidelity simulation learning as alternative clinical bedside training during COVID-19 pandemic. A qualitative thematic analysis approach was employed through direct focus group discussions. Transcripts were thematically analyzed using Marshall and Rossman's (1999) process. Thirty-five nursing students joined seven focus group discussions. Two major themes emerged from data analysis as follow: "Restored factual training environment", and "Proficiency devoid from self-confidence". Students articulated the implication of using HFS on their knowledge, practical skills, communication, and team working. However, a criticism on HFS inability to promote self-confidence was addressed. Despite the effectiveness of HFS in nursing education, it was viewed as incompetent for building sufficient confidence required for direct interaction with contagious patients in real settings.